A study on patterns of breakfast eating habit and the reasons of breakfast skipping among students at SMK Seksyen 9 and SMK Seksyen 24 (1) Shah Alam / Siti Hajar Mat Isa - Mat Isa, Siti Hajar (2014)
Nutritional and health status have a strong influence on cognitive and psychomotor abilities of students. However, healthy eating habits among students still less applied particularly breakfast consumption. This study aims to identify patterns of eating breakfast through the consistency of breakfast consumption, attitudes toward eating breakfast, the awareness and the reasons of breakfast skipping among school students. This study used questionnaires as an instrument to collect the data. A total of 80 respondents consisting of high school students from SMK Seksyen 9 and SM.K Seksyen 24 (1) were randomly selected. Data were analyzed descriptively and inferential statistical using SPSS version 20.0. The results show that most of the students eat breakfast every day at home and school. Moreover, students were like to consume milk and oatmeal during breakfast. There is a weak relationship between attitudes toward eating breakfast and the frequency of eating breakfast in a week. Besides that, there is no significant difference between SMK Seksyen 9 and SMK Seksyen 24(1) in terms of frequency of eating breakfast in a week, races and types of food consumed for breakfast. The finding shows that some students feel kind of hungry and extremely hungry if they do not eat breakfast. Awareness about the important of eating breakfast is also high among students which are more than 90%. The most reasons of breakfast skipping among school students are there is not enough time to eat breakfast before class, do not like food for breakfast, and trying to lose weight.